Acquired stuttering - Harley, Jane (Henry Stewart Talks, 2016)
Definition of stuttering, Developmental stuttering, Acquired stuttering, Terminology, State of the research, Acquired neurogenic stuttering, Acquired psychogenic stuttering, Assessment: building a clinical picture, Management, General principles of working